Digital Leadership and Social Media in Indonesian Regional Government: A Literature Study from West Java Province - Bambang Widiyahseno; Della Anggun Mutiara; Fidela Maharani Angelica; Firnanda Ayu Noer Fadhila; Yusuf Adam Hilman (Journal of Research in Social Science and Humanities, 2025)
The rapid development of information and communication technology has fundamentally reshaped governance practices, particularly in how regional leaders communicate with the public. Digital leadership has emerged as a critical factor in enhancing transparency, public participation, and political legitimacy within regional government contexts. This study examines the role of digital leadership in regional governance through the lens of social media utilization, focusing on West Java Province, Indonesia. A library research method was employed, drawing on scientific journals, academic articles, national news sources, and relevant official social media platforms published within the past five years. Data were analyzed using a descriptive qualitative approach, with information organized thematically according to digital leadership practices, public communication strategies, and community interaction patterns. The findings reveal that social media platforms, particularly YouTube, Instagram, and TikTok, function as effective instruments of public communication, enabling rapid, transparent, and interactive dissemination of governance-related information. The digital leadership practices observed are characterized by a conversational communication style, direct engagement with community members, and the integration of local Sundanese cultural values into digital content. These practices strengthen emotional proximity between leaders and the public while building an image of responsive governance. The study also highlights that, although social media significantly enhances leadership legitimacy, its effectiveness depends on ethical and consistent use grounded in genuine governance performance.